Effect of Jigsaw Teaching Approach on Students’ Academic Achievement in Business Education Practicum : A Case Study in Colleges of Education, South East Nigeria - Okeke, Amaka Ukamaka; Dikeocha, Lucy Udoka (Journal of Pedagogy and Education Science, 2024)
This study focused on the effect of jigsaw teaching approach on students’ academic achievement in business education practicum in colleges of education South-East, Nigeria. Two research questions guided the study while three hypotheses were tested. The study adopted quasi experimental research design of pretest, post-test non-randomized group. The study area is South-East Nigeria. The population of the study comprised 155 Business Education NCE II students from the seven colleges of education in South-East, Nigeria. The sample of the study is 67 NCE II Business Education students from two colleges of education in South-East, Nigeria. A Business Education Practicum Achievement Test (BEPAT) was developed by the researchers as to enable them collect data for the study. The instrument was validated by experts and subsequently administered to the 67 respondents used for the study. The administered test instrument were retrieved, marked and scored and the scores used for analysis. The items with regards to research questions were analyzed using mean and standard deviation while alternative hypotheses were tested at 0.05 level of significance using Analysis of Covariance. Findings of the study revealed that teaching and learning business education practicum using jigsaw teaching approach improve students’ academic achievement. Result of the hypotheses shows that there was no significant difference between the academic achievement of male and female NCE II students in business education practicum. Findings on the interaction effect of teaching approaches and gender indicates that gender interact to affect students’ achievement in business education practicum. The researcher concluded that jigsaw teaching approach is effective in improving students’ achievement in business education practicum irrespective of gender.